Comparative evaluation of nine faecal immunochemical tests for the detection of colorectal cancer - Tao, Sha; Seiler, Christoph; Ronellenfitsch, Ulrich; Brenner, Hermann (Acta oncologica, 2013)
Background. Faecal immunochemical tests (FITs) for haemoglobin are increasingly used for non-invasive screening for colorectal cancer (CRC) but large scale comparative studies of different FITs for detection of CRC, overall and by stage, are sparse. We aimed to determine and compare performance of different FITs for the detection of CRC, and to assess their stage-specific sensitivities. Material and methods. We assessed sensitivity, specificity and their corresponding 95% confidence intervals for six qualitative FITs among 74 CRC cases (59% stage I or II cancers) and 1480 controls free of colorectal neoplasm. Overall and stage-specific receiver operating characteristic curves were derived for three quantitative FITs. The areas under the curves (AUCs) were calculated and compared. Results. Pairs of overall sensitivity and specificity of the qualitative FITs ranged from 66% and 96% to 92% and 62%, respectively. For the three quantitative tests, AUCs ranged from 0.90 to 0.92, with sensitivities ranging from 80% to 87% at cut-offs yielding 90% specificity. AUCs ranged from 0.85 to 0.92, 0.94 to 0.96, and 0.86 to 0.93 for stage I, stage II and advanced stages (stage III and IV) cancers, respectively. At a specificity of 90%, the tests detected 65%-85% of stage I cancers. Conclusion. The diagnostic performance of FITs regarding detection of CRC is promising, even though the pre-defined cut-offs of some of the qualitative FITs need to be adjusted to limit false-positive rates in screening setting. At cut-off levels yielding 90% specificity, the quantitative tests detected the vast majority of CRCs, even at early stages.
Gesehen am 31.01.2022